Long‐distance dispersal and inter‐island colonization across the western Malagasy Region explain diversification in brush‐warblers (Passeriformes: Nesillas). (20th June 2016) - Fuchs, Jerome; Lemoine, Delphine; Parra, Juan Luis; Pons, Jean‐Marc; Raherilalao, Marie Jeanne; Prys‐Jones, Robert; Thebaud, Christophe; Warren, Ben H.; Goodman, Steven M.
Abstract : The present study examines the colonization history and phylogeography of the brush‐warblers ( Nesillas ), a genus of passerines endemic to islands of the western Indian Ocean (Madagascar, Comoros, and Aldabra Atoll). The phylogeny of all recognized Nesillas taxa was reconstructed employing Bayesian phylogenetic methods and divergence times were estimated using a range of substitution rates and clock assumptions. Spatiotemporal patterns of population expansion were inferred and niches of different lineages were compared using ecological niche modelling. Our results indicate that taxa endemic to the Comoros are paraphyletic and that the two endemic species on Madagascar ( Nesillas typica and Nesillas lantzii ) are not sister taxa. The brush‐warblers started to diversify approximately 1.6 Mya, commencing with the separation of the clade formed by two species endemic to the Comoros ( Nesillas brevicaudata and Nesillas mariae ) from the rest of the genus. The lineages leading to the two Malagasy species diverged approximately 0.9 Mya; each with significantly different modern ecological niches and the subject of separate demographic processes. Patterns of diversification and endemism in Nesillas were shaped by multiple long distance dispersal events and inter‐island colonization, a recurring pattern for different lineages on western Indian Ocean islands. The diversification dynamics observed for Nesillas are also consistent with the taxon cycle hypothesis.